Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1093/europace/eum045
|View full text |Cite
|
Sign up to set email alerts
|

Is there an anatomical substrate for idiopathic paroxysmal atrial fibrillation? A case–control echocardiographic study

Abstract: Patients with idiopathic AF showed larger left atria when compared with controls, there being no differences between patients with a first episode or a recurrence. This suggests the presence of an enhanced substrate to develop idiopathic lone AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
1
24
0
3
Order By: Relevance
“…AF is a progressive condition that begins with hemodynamic and/or structural changes in the LA and evolves throughout the paroxysmal and persistent stage [25]. LA enlargement has been widely related to AF, both in chronic AF and in paroxysmal AF [27,28]. In the present study, patients with silent AF showed only a trend towards LA enlargement (indexed LA volume 37.4 vs. 30.8 ml/m 3 , p = 0.057).…”
Section: Discussionmentioning
confidence: 99%
“…AF is a progressive condition that begins with hemodynamic and/or structural changes in the LA and evolves throughout the paroxysmal and persistent stage [25]. LA enlargement has been widely related to AF, both in chronic AF and in paroxysmal AF [27,28]. In the present study, patients with silent AF showed only a trend towards LA enlargement (indexed LA volume 37.4 vs. 30.8 ml/m 3 , p = 0.057).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Despite the contribution of LA enlargement to the occurrence and progression of AF, 10-13 the assessment of LA volume (LAV)-the most robust marker of LA sizeis not recommended for routine use in risk evaluation, because its predictive value seems lower than expected. 14,15 LA functional evaluation might improve the identification of patients at risk for AF.…”
mentioning
confidence: 99%
“…Так, M. Sitges et al (2007 г.) выявили снижение систо-лических миокардиальных скоростей (s) фиброз-ного кольца МК у пациентов с ФП в сравнении со здоровыми добровольцами [14]. Аналогичная тенденция отмечена и в нашем исследовании.…”
Section: Discussionunclassified